Application of Grouping Methods To Assess Growth and Development in The EU Member States - Roszko-Wójtowicz, Elżbieta Marlena; Białek, Jacek (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Voting methods allow to create a synthetic (global) rank of analyzed objects basing on ranks coming from independent experts. The aim of the paper is ordering of the EU member countries according to their level of economic development. The self‑developed rating takes as a starting point well‑known in the literature international indices. We consider ranks based on the following indices: i.e. Global Innovation Index, Global Creativity Index, Global Competitiveness Index, Summary Innovation Index, Innovation Output Indicator. Selected synthetic measures were classified into four groups: innovativeness, competitiveness, entrepreneurship and knowledge. Borda’s and Dodgson’s grouping methods are applied for a creation of a synthetic (global) rank. All calculations are made in the original computer program. Conducted analysis confirms that synthetic (global) rank is closer to assessment of the overall level of socio‑economic development rather that simple economic growth. Achieved results show strong correlation between synthetic (global) rank and selected international indices. Simultaneously, there is a significant discrepancy between synthetic (global) rank and countries ordering according to GDP per capita.